1996
DOI: 10.1006/jsco.1996.0009
|View full text |Cite
|
Sign up to set email alerts
|

Unification in the Union of Disjoint Equational Theories: Combining Decision Procedures

Abstract: Most of the work on the combination of uni cation algorithms for the union of disjoint equational theories has been restricted to algorithms which compute nite complete sets of uni ers. Thus the developed combination methods usually cannot be used to combine decision procedures, i.e., algorithms which just decide solvability of uni cation problems without computing uni ers. In this paper we describe a combination algorithm for decision procedures which works for arbitrary equational theories, provided that sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 23 publications
(6 reference statements)
0
44
0
Order By: Relevance
“…He has not restricted theories to have any particular type, instead he showed that all equational theories E 1 , E 2 over disjoint signatures that have decidable constant elimination problems admit a combination procedure. This result was improved by Baader and Schulz in [3,4]. They showed that all equational theories E 1 , E 2 over disjoint signatures having decidable E 1 -and E 2 -unification problems with linear constant restrictions admit a combination procedure.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…He has not restricted theories to have any particular type, instead he showed that all equational theories E 1 , E 2 over disjoint signatures that have decidable constant elimination problems admit a combination procedure. This result was improved by Baader and Schulz in [3,4]. They showed that all equational theories E 1 , E 2 over disjoint signatures having decidable E 1 -and E 2 -unification problems with linear constant restrictions admit a combination procedure.…”
Section: Introductionmentioning
confidence: 83%
“…They showed that all equational theories E 1 , E 2 over disjoint signatures having decidable E 1 -and E 2 -unification problems with linear constant restrictions admit a combination procedure. Since Eunification with linear constant restrictions is equivalent to general E-unification, the result from [3,4] cannot be improved.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…These linear constraints are similar to the linear constant restrictions of [7]. The following two theorems relate the unification problem S over ACUID l to its h-image T over ACUIH (recall that H denotes the set of homomorphisms H (S)).…”
Section: Definition 2 (I) a Substitution Is Deciduous If Each Variabmentioning
confidence: 96%